2013
DOI: 10.1590/s1677-54492013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento endovascular de aneurisma de aorta abdominal em paciente com rim em ferradura: relato de caso

Abstract: Horseshoe kidney is one of the most common urologic anomalies, present in about 0.12% of patients with abdominal aortic aneurysm. Conventional surgical repair is associated with technical difficulties that probably increase morbidity and mortality but can be avoided with endovascular treatment. We report the case of a 64-year-old patient presenting with horseshoe kidney and abdominal aortic aneurysm and successfully treated with endovascular repair.Keywords: abdominal aortic aneurysm; congenital abnormalities;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 16 publications
0
2
0
14
Order By: Relevance
“…Duas técnicas principais são frequentemente empregadas na cirurgia aberta de AAA: a substituição do segmento dilatado da aorta por um enxerto sintético e a técnica de clampagem transperitoneal ou retroperitoneal 1,6 .…”
Section: Abordagens Técnicas Em Cirurgia Aberta De Aneurisma De Aorta...unclassified
See 2 more Smart Citations
“…Duas técnicas principais são frequentemente empregadas na cirurgia aberta de AAA: a substituição do segmento dilatado da aorta por um enxerto sintético e a técnica de clampagem transperitoneal ou retroperitoneal 1,6 .…”
Section: Abordagens Técnicas Em Cirurgia Aberta De Aneurisma De Aorta...unclassified
“…Isso pode envolver a realização de uma laparotomia para acessar a aorta e, em seguida, implantar um stent-graft endovascular para reforçar a parede da aorta. Essa abordagem híbrida é especialmente útil em casos de aneurismas complexos ou em pacientes com anatomia aórtica desafiadora, permitindo uma reparação mais precisa e minimizando o trauma cirúrgico 2,6 .…”
Section: Técnica De Clampagem Transperitoneal Ou Retroperitonealunclassified
See 1 more Smart Citation
“…This study cooperate especially in surgical interventions, as well as in renal transplants and radiological studies. [9][10][11] The objective of the present study is to report the arteriovenous pattern found in the renal hilum in a case of horseshoe kidney.…”
Section: Introductionmentioning
confidence: 99%
“…2 Treatment of AAA in a patient with a horseshoe kidney involves certain peculiarities: 1) the renal parenchyma covering the AAA; 2) anomalies of renal arterial supply; and 3) anomalies related to the urinary collector system. 3…”
Section: Introductionmentioning
confidence: 99%